VIBRATION MODAL ANALYSIS AND RESEARCH OF CANTILEVER BEAM BASED ON POLY IIR METHOD - ZHANG Min; ZHANG Yi; HOU YaoHua; MA GuangXuan (Jixie qiangdu)
This paper analyses the vibration modes of a simply supported beam with vibration table. Firstly,the one dimensional vibration theory is used to acquire the beam vibration mathematical model. Following to use Bernoulli Euler beam theory to calculate the beam vibration differential equation,in addition to the beam set specific boundary constraint conditions to calculate each order modal parameters,using the Workbench beam finite element simulation analysis for the first five order natural frequency and vibration mode. In the end,the experimental modal algorithm based on Poly IIR is applied to identify the modal parameters of simply supported beam. The modal frequencies and mode shapes are obtained in this paper. It is keeping 3%about the consistency of the simulation value and experiment result,Which can subsequent beam or plate and so on EMA elastomer complex structure analysis and research to provide certain reference.